Converging circuits between pain and depression: the ventral tegmental area as a therapeutic hub - Flores-García, Montse; Rizzo, Arianna; Garçon-Poca, Maria Zelai; Fernández-Dueñas, Víctor; Bonaventura, Jordi (Frontiers in Pharmacology, 2023)
Chronic pain and depression are highly prevalent pathologies and cause a major socioeconomic burden to society. Chronic pain affects the emotional state of the individuals suffering from it, while depression worsens the prognosis of chronic pain patients and may diminish the effectiveness of pain treatments. There is a high comorbidity rate between both pathologies, which might share overlapping mechanisms. This review explores the evidence pinpointing a role for the ventral tegmental area (VTA) as a hub where both pain and emotional processing might converge. In addition, the feasibility of using the VTA as a possible therapeutic target is discussed. The role of the VTA, and the dopaminergic system in general, is highly studied in mood disorders, especially in deficits in reward-processing and motivation. Conversely, the VTA is less regarded where it concerns the study of central mechanisms of pain and its mood-associated consequences. Here, we first outline the brain circuits involving central processing of pain and mood disorders, focusing on the often-understudied role of the dopaminergic system and the VTA. Next, we highlight the state-of-the-art findings supporting the emergence of the VTA as a link where both pathways converge. Thus, we envision a promising part for the VTA as a putative target for innovative therapeutic approaches to treat chronic pain and its effects on mood. Finally, we emphasize the urge to develop and use animal models where both pain and depression-like symptoms are considered in conjunction.